2023
DOI: 10.3390/app13127180
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Self-Selected Music during Warm-Up Improves Anaerobic Performance through Enhancement of the Excitability of the Cerebral Cortex

Abstract: The study investigated the effects of listening to self-selected music during a warm-up on brain wave synchronization/desynchronization and Wingate test performance. Seventeen healthy young men were required to complete a 10 min warm-up session with or without music intervention, followed by an electroencephalogram (EEG) or Wingate test, respectively. The ratings of perceived exertion (RPE) and heart rate (HR) were recorded immediately after the Wingate test. Compared with no music intervention, listening to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Hormones that have a balancing and regulating effect on human physiology positively affect the physical performance of individuals (26). When the literature is examined in the light of these data, there are many studies showing that music positively affects sportive parameters such as warm-up (27), aerobic power (28), anaerobic power (29,30), and strength (31). Svoboda et al reported that the fast music group exhibited higher athletic performance in a study conducted with 3 different groups of fast music, slow music and no music at a self-selected music tempo (31).…”
Section: Discussionmentioning
confidence: 99%
“…Hormones that have a balancing and regulating effect on human physiology positively affect the physical performance of individuals (26). When the literature is examined in the light of these data, there are many studies showing that music positively affects sportive parameters such as warm-up (27), aerobic power (28), anaerobic power (29,30), and strength (31). Svoboda et al reported that the fast music group exhibited higher athletic performance in a study conducted with 3 different groups of fast music, slow music and no music at a self-selected music tempo (31).…”
Section: Discussionmentioning
confidence: 99%
“…One researcher verified that participants remained seated during the whole test, particularly during the initial phase of the sprint. Peak and minimum cycling power were used to calculate the Wingate fatigue index (%) as previously suggested [ 55 , 56 , 57 ]. Researchers were blinded to conditions during the gathering of data and calculation of performance data.…”
Section: Methodsmentioning
confidence: 99%